Acoustic emission characteristics and fracture mechanism of sandstone in open-pit mines under different types of cyclic loads - Zhang, Qing; Zhang, Ling; Jiang, Xutong (Frontiers in Earth Science, 2024)
Rock mass is one of the most important load-bearing media in geotechnical engineering. It has been continually vulnerable to geological tectonic movements, natural calamities, and human excavation activities. Its inherent weak surfaces such as primary pores, joints, and fissures have resulted in varying damage degrees. In mining operations, the damaged rock mass has a variety of negative impacts on the stability of its overlying structures and is frequently disturbed by the load. To study the damage law of rock mass under cyclic loading, in this paper, an acoustic emission (AE) device was employed to monitor the rock under the action of two types of cyclic loads: the variable upper and lower pre-loads, and the fixed upper and lower pre-loads. The damage of the loaded rock was split into three stages in this research, based on the features of the AE signals of the rock under uniaxial load, and the damage evolution of the loaded rock was analyzed in distinct stages. The AE signals of the rock under cyclic loading were mainly emitted in the first loading stage. When the stress did not exceed the maximum stress value in the stress history of the loaded rock, few new AE event was generated in the loaded rock. After the low-frequency cyclic static load, the AE signals varied with the load-bearing stress of the rock during the whole process from initial loading to failure, which was consistent with the characteristics of the AE signals of the loaded rock. The research results can be adapted to rock mass in open-pit mines stability analysis and risk prediction while providing some references for the early warning and danger relief of rock masses in engineering.